Rodina, manželství a příbuzenství u cikánských skupin v ČR a v zahraničí - Lenka Budilová (AntropoWebzin)
The article deals with the topic of family, marriage and kinship in “Roma/Gypsy” groups in Europe and North America and offers an overall overview of the scholarly literature on this topic.The basic themes, theoretical concepts and perspectives in anthropological and sociological literature on “Roma/Gypsy” kinship, marriage and family are discussed in the text. The distinction is made between the Czech and Slovak academic writings (with the focus on individual sholars and topics developed in their texts) and the foreign literature (here the overview is mostly confined to works and texts published in English). The aim of the text is to provide to students the basic facts and summary of the texts published in this field and the most important topics (domestic units, character of kinship, marriage alliances, endogamy, brideprice, etc.) that have been discussed in the last several decades. Special attention is paid to the modern approaches discussing kinship and family in their connection to the concepts of locality, identity, ethnicity and gender.